Case report: Cryoablation as a novel bridging strategy prior to CAR-T cell therapy for B cell malignancies with bulky disease - Zhang, Xiaomin; Wu, Jinming; Qiao, Liangliang; Chen, Lixuan; Chen, Chaolin; Zhang, Hui; Luo, Rongcheng; Xiao, Yang (Frontiers in Oncology, 2023)
Chimeric antigen receptor (CAR) T-cell therapy has emerged as a powerful immunotherapy in relapsed/refractory (R/R) hematological malignancies, especially in R/R B-cell acute lymphocytic leukemia (B-ALL), non-Hodgkin lymphoma (NHL), and multiple myeloma (MM). To prevent disease progression and reduce tumor burden during CAR-T cell manufacturing, bridging therapies prior to CAR-T cell infusion are crucial. At present, it has been demonstrated that targeted therapy, radiotherapy and autologous stem cell transplantation (ASCT) could serve as effective bridging strategies. However, whether cryoablation could serve as a novel bridging strategy is unknown. In this paper, we report 2 cases of R/R B cell malignancies with bulky disease that were successfully treated with a combination of cryoablation and CAR-T cell therapy. Patient 1 was a 65-year-old female who was diagnosed with R/R MM with extramedullary disease (EMD). She was enrolled in the anti-BCMA CAR-T cell clinical trial. Patient 2 was a 70-year-old man who presented with a subcutaneous mass in the right anterior thigh and was diagnosed with primary cutaneous diffuse large B cell lymphoma, leg type (PCLBCL-LT) 1 year ago. He failed multiline chemotherapies as well as radiotherapy. Thus, he requested anti-CD19 CAR-T cell therapy. Unfortunately, they all experienced local progression during CAR-T cell manufacturing. To rapidly achieve local tumor control and reduce tumor burden, they both received cryoablation as a bridging therapy. Patient 1 achieved a very good partial response (VGPR) 1 month after CAR-T cell infusion, and patient 2 achieved a partial response (PR) 1 month after CAR-T cell infusion. In addition, adverse effects were tolerable and manageable. Our study demonstrated the favorable safety and efficacy of combination therapy with cryoablation and CAR-T cell therapy for the first time, and it also indicates that cryoablation could serve as a novel therapeutic strategy for local tumor control in B cell malignancies.